2022
DOI: 10.3389/fcvm.2022.824955
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic value of the PDW/HDL-C ratio in patients with chest pain symptoms and coronary artery calcification

Abstract: BackgroundPlatelet-related parameters and HDL-C have been regarded as reliable and alternative markers of coronary heart disease (CHD) and the independent predictors of cardiovascular outcomes. PDW is a simple platelet index, which increases during platelet activation. Whether the PDW/HDL-C ratio predicts major adverse cardiovascular and cerebrovascular events (MACCEs) in patients who complained of chest pain and confirmed coronary artery calcification remains to be investigated. This study aimed to investigat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 27 publications
0
1
0
Order By: Relevance
“…HDL, as a cholesterol receptor, can promote cholesterol out ow and participating in activation of platelets in cardiovascular diseases. 24 Even though studies usually reported an inhibition of HDL on platelet activation in cardiovascular events at long-time follow-up, 25,26 Deanna L Plubell et al reported a dynamic changes of HDL in acute phase of stroke associate with recovery, 27 which may related with in ammatory remodeling. The positive correlation of PDW and HDL-C in ITP implied the regulatory potential of HDL-C in platelet status in ITP.…”
Section: Discussionmentioning
confidence: 99%
“…HDL, as a cholesterol receptor, can promote cholesterol out ow and participating in activation of platelets in cardiovascular diseases. 24 Even though studies usually reported an inhibition of HDL on platelet activation in cardiovascular events at long-time follow-up, 25,26 Deanna L Plubell et al reported a dynamic changes of HDL in acute phase of stroke associate with recovery, 27 which may related with in ammatory remodeling. The positive correlation of PDW and HDL-C in ITP implied the regulatory potential of HDL-C in platelet status in ITP.…”
Section: Discussionmentioning
confidence: 99%